Peningkatan Hasil Belajar Siswa Menggunakan Strategi Pembelajaran Berbasis Multiple Intelligence (Kecerdasan Majemuk) pada Mata Pelajaran Tematik Sekolah Dasar - Fauzi, Hasan; Yusnita, Yusnita; Sugito, Wahyu; Yurnalis, Yurnalis; Santoso, Sigit (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2023)
As a teacher, you are constantly required to master the following things, understand and formulate learning objectives, understand the learning process, understand how to deliver lessons to students, be able to choose learning aids and media, be able to understand and provide services to individual differences of students, able to provide guidance to students, able to compile and use evaluation tools Each student has differences between individuals with one another. So on the basis of understanding the condition of students, the application of learning strategies must be able to provide opportunities for students to develop the potential that exists within themselves. The teacher as an educator who plays a role in the ongoing learning process has a responsibility in determining learning strategies. This research was conducted at SD Negeri 023 Belantaraya with 15 students. This type of research is classroom action research. After learning by using learning strategies based on multiple intelligences in cycle 1 and cycle 2, student learning outcomes have increased with the following results the completeness of student learning outcomes is 46.67% of students complete and 53.33% not complete then there is an increase in students who complete in student learning outcomes after applying multiple intelligence-based strategies with 93.33% of students completing learning and 6.67% of students not being complete in learning outcomes.